The Impact of Government Guarantees on Bond Spreads: an Empirical Study of State-Owned Enterprises in Southeast Asia - Naomi Lamria Rismauli (Eduvest - Journal of Universal Studies, 2025)
The recent financial distress among construction firms in Southeast Asia, including Indonesia’s state-owned enterprises (BUMN Karya) underscores significant challenges in infrastructure financing, particularly in relation to elevated borrowing costs and constrained access to capital markets. In this context, government guarantees are commonly perceived as mechanisms to mitigate credit risk and compress bond spreads, defined as the yield differential between corporate bonds and risk-free benchmarks such as sovereign bonds. This study investigates the effect of government guarantees on bond spreads among BUMN Karya, focusing on Indonesia as a case study. It also examines the moderating role of the Altman Z-score as a proxy for corporate financial stability. Employing a quantitative approach with secondary data spanning 2017 to 2023, the analysis utilizes a multiple linear regression model. The findings reveal that government guarantees do not exert a statistically significant influence on bond spreads, nor does the Altman Z-score significantly moderate this relationship. These results suggest that despite theoretical expectations, investors continue to perceive BUMN Karya bonds as high-risk instruments, largely due to macroeconomic uncertainties such as inflationary pressures and restrictive monetary policies. The study highlights the need for enhanced governance, greater transparency, and macroeconomic stability to bolster the credibility and effectiveness of government guarantee schemes in reducing corporate borrowing costs.